Endoscopic submucosal resection: a technique using novel devices for incision and resection of neoplastic lesions - Metter, Klaus; Aepli, Patrick; Dumoulin, Franz Ludwig; Hayee, Bu'Hussain; Grund, Karl-Ernst; Farin, Günter; Frei, Remus (Endoscopy, 2022)
Background Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are established techniques for treatment of superficial gastrointestinal neoplasia. Limitations of EMR are low en bloc resection rates for larger lesions, resulting in frequent recurrences. Major disadvantages of ESD are technical difficulty and long procedure times. We evaluated technical feasibility and safety of newly designed devices for en bloc resection of lesions measuring 20–40 mm in a technique called endoscopic submucosal resection (ESR).Methods This case series included 93 lesions from different locations (11 stomach, 25 colon, 57 rectum) with a median size of 29 mm (range 10–70). ESR was performed using two novel instruments for circumferential mucosal incision and deep submucosal resection, respectively.Results Resection by ESR was feasible in all cases. En bloc and R0 rates were insufficient when ESR was attempted without prior circumferential mucosal incision, but were 70 % and 63 %, respectively, when mucosal incision was done before application of the submucosal resection device. We observed three complications (two delayed bleedings, one microperforation) but no cases of emergency surgery or 30-day mortality.Conclusions Results demonstrated feasibility and excellent safety of ESR using two novel devices for en bloc resection of early gastrointestinal neoplasia. The technique offered relative technical ease and high efficacy.